Application of Control Chart for Defect Control in Asinan and Rujak Ciamix Based on POM-QM - Camelia Rizki Agrina; Luthfia Qolbi Salima (International Journal of Management and Business Economics, 2025)
This study aims to control defect rates in the production process of Asinan and Rujak Ciamix, a product of a micro, small, and medium enterprise (MSME), using control chart methods supported by POM-QM software. Primary data were collected from production volumes and defect occurrences during the production process in November 2024. The analysis revealed that the defect rate remained within control limits, despite the occurrence of defects such as overly sour taste, hard texture, and burnt sugar. The implementation of control charts facilitated real-time monitoring of the production process, enhanced operational efficiency, and supported accurate data-driven decision-making. This study demonstrates that integrating control chart methods with POM-QM software can assist MSMEs in maintaining process stability, minimizing product defects, and improving quality consistency to meet customer expectations. The findings underscore the potential of this approach to enhance quality management practices in MSME production processes.